BUDIDAYA SAYURAN ORGANIK DENGAN POLYBAG UNTUK MENINGKATKAN KETAHANAN PANGAN DI DESA PEGUYANGAN KAJA, KECAMATAN DENPASAR UTARA - Ni Ketut Ayu Juliasih; Ni Wayan Merliana Dewi; Ni Luh Gede Suastini; I Dewa Gede Yoga Sedana (JURNAL SEWAKA BHAKTI, 2021)
The 2021 Unhi KKN-PPM activity, in Peguyangan Kaja Village, Denpasar City, Bali Province was carried out for 5 weeks, (27 August to 30 September 2021). One of the KKN-PPM programs implemented is the food security program in the form of organic vegetable cultivation activities with polybags. This activity was adapted to the KKN-PPM theme that was carried, namely "Village, Kala Tattwa: Ausadhining Bhumi" which means Glorifying Plants in Bhumi according to the place, time, and local wisdom. The purpose of this activity is to provide knowledge, skills about organic vegetable cultivation using polybag planting media, as well as to develop a conservative attitude to care for the environment to the community during the Covid-19 pandemic. The method used in this activity is a participatory method involving members of the Bija Utama Farmer Group facilitated by Unhi KKN-PPM students. The type of vegetable grown in this activity is cayenne pepper (Capsicum frutescens L.). In addition to daily food needs, red chili also has high economic value, and can be used as an ornamental plant. The material given is in the form of planting media used, media composition, and planting containers using polybags. Conclusion: the community gains knowledge and understanding about the cultivation of cayenne pepper vegetables with polybags as an effort to maintain food security, which is important to be carried out further in daily activities so that people can remain productive during the Covid-19 pandemic. The type of vegetable grown in this activity is cayenne pepper. In addition to daily food needs, red chili also has high economic value, and can be used as an ornamental plant. The material provided is in the form of planting media used, media composition, and planting containers using polybags